2003
DOI: 10.1038/oby.2003.182
|View full text |Cite
|
Sign up to set email alerts
|

Which Metric of Relative Weight Best Captures Body Fatness in Children?

Abstract: FIELD, ALISON E., NAN LAIRD, EMILY STEINBERG, ERICA FALLON, MARIAMA SEMEGA-JANNEH, AND JACK A. YANOVSKI. Which metric of relative weight best captures body fatness in children? Obes Res. 2003;11: 1345-1352. Objective: To evaluate the relative merits of BMI (kilograms per meter squared) and age-and gender-adjusted BMI, age-and gender-specific z score of BMI, and age-and gender-specific percentiles of BMI as surrogate measures of body fatness among a sample of youth. Research Methods and Procedures:The sample c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
77
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(84 citation statements)
references
References 18 publications
6
77
1
Order By: Relevance
“…Therefore, BMI 85 percentiles, one of the most sensitive indicators for adiposity in children, can be useful for screening obesity, as has been suggested in another study. 7 Although intrinsically different from BMI in the method of obesity identification, PWH was a better indicator than the IOTF-BMI criteria in terms of measurement accuracy in our study. As both measures were based on the population-specific standard, we suggest that the value of the population-specific standard in defining children's obesity needs to be reconsidered.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Therefore, BMI 85 percentiles, one of the most sensitive indicators for adiposity in children, can be useful for screening obesity, as has been suggested in another study. 7 Although intrinsically different from BMI in the method of obesity identification, PWH was a better indicator than the IOTF-BMI criteria in terms of measurement accuracy in our study. As both measures were based on the population-specific standard, we suggest that the value of the population-specific standard in defining children's obesity needs to be reconsidered.…”
Section: Discussioncontrasting
confidence: 52%
“…Previous studies comparing various criteria for anthropometric measurements in childhood with body fat measures suggested that IOTF-BMI cutoffs may have low sensitivity, 6 and that BMI percentile X85 percentile is useful for identifying children who may be over-fat. 7 Therefore, the aim of the study was twofold. First, we compared the validity of various criteria of childhood obesity in Korean pre-adolescent school children, based on the percentage body fat (PBF): the local BMI, the local PWH and the IOTF-BMI criteria.…”
Section: Introductionmentioning
confidence: 99%
“…BMI is commonly used in adults and more recently recommended for use in children and adolescents (Power et al, 1997;Bellizzi and Dietz, 1999;Dietz and Bellizzi, 1999;Bini et al, 2000;Reilly et al, 2000;Widhalm et al, 2001). However, the assessment of weight status in young people is more complex, when using BMI to assess adiposity in children and adolescents it is essential that age-and sex-specific BMI cutoffs be used to define overweight and obesity (Widhalm et al, 2001;Field et al, 2003). Given the economic, environmental, genetic and nutrition influences on body size, having growth standards that are nationally representative is an important consideration (Livingstone, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…It is much less expensive than using DEXA, airdisplacement plethysmography, or The test characteristics for use of BMI for screening for childhood obesity are generally adequate when viewed from the perspective of correlation with gold-standard methods for measuring body composition and tracking coefficients. 15 The test characteristics are less good but probably still acceptable when the objective is to predict outcomes in adulthood. 7,16 …”
Section: Benefits Of Bmimentioning
confidence: 99%